Dinosaurs and other reptiles from the Mesozoic of Mexico - Rivera-Sylva, Héctor E. (Indiana University Press, 2014)
Cover; Dinosaurs and Other Reptiles from the Mesozoic of Mexico; Title; Copyright; Dedication; Contents; Contributors; Acknowledgments; Preface; 1 History of the Discoveries of Dinosaurs and Mesozoic Reptiles in Mexico; 2 Paleogeography and Paleoenvironment of Mexico during the Mesozoic; 3 Turtles of the Mesozoic of Mexico; 4 Mesozoic Lepidosauromorphs of Mexico: A Review and Discussion of Taxonomic Assignments; 5 Plesiosaurs, Reptiles between Grace and Awe; 6 Mexican Ichthyosaurs; 7 Overview of Mesozoic Crocodyliforms from Mexico; 8 Mexican Pterosaurs-Rare Jewels in the Fossil Record
Description based upon print version of record
Keywords: Electronic books; Paläontologie; Fossil; Fossile Reptilien; Mesozoikum; Mexiko; Dinosaurier